2006
DOI: 10.1021/bi0613224
|View full text |Cite
|
Sign up to set email alerts
|

Functional Homodimers and Heterodimers of Recombinant Smooth Muscle Tropomyosin

Abstract: Skeletal and smooth muscle tropomyosin (Tm) require acetylation of their N termini to bind strongly to actin. Tm containing an N-terminal alanine serine (AS) extension to mimic acetylation, has been widely used to increase binding. The current study investigates the ability of an N-terminal AS extension to mimic native acetylation for both αα and ββ smooth Tm homodimers. We show that : 1) ASα-Tm binds actin 100 fold tighter than α-Tm, and 2 fold tighter than native smooth αβ-Tm; 2) β-Tm requires an AS extensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 30 publications
(55 reference statements)
2
37
0
Order By: Relevance
“…These data are consistent with the finding that only Tms with a low K T (i.e. smooth muscle Tm and fibroblast Tm) are capable of complementing Cdc8 function in vivo, providing strong evidence that unlike the budding yeast Tms, Cdc8 has essential roles in regulating myosin function in addition to stabilising actin filaments (Balasubramanian et al, 1992;Coulton et al, 2006;Maytum et al, 2001).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These data are consistent with the finding that only Tms with a low K T (i.e. smooth muscle Tm and fibroblast Tm) are capable of complementing Cdc8 function in vivo, providing strong evidence that unlike the budding yeast Tms, Cdc8 has essential roles in regulating myosin function in addition to stabilising actin filaments (Balasubramanian et al, 1992;Coulton et al, 2006;Maytum et al, 2001).…”
Section: Discussionsupporting
confidence: 89%
“…We have not yet determined whether any of the nonendogenous Tms are acetylated in fission yeast, but the fact that only smooth Tm can bind to actin in the absence of Nterminal modification whereas Tpm1, Tpm2 and skeletal Tm do not (Coulton et al, 2006;Maytum et al, 2001) may explain why only smooth muscle Tm was able to function in yeast (Fig. 4A,B).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have observed that an increment in tropomyosin expression partially restores functional defects in actin stress fibers (31,37). In contrast, Tpm1 overexpression in wildtype HeLa cells significantly reduced the area and number of focal adhesions, in agreement with other expressed tropomyosin isoforms (38) and suggestive of a compromised Tpm1 function, most probably by its reduced Nt-acetylation.…”
Section: Tpm1 Overexpression Partially Restores Actin Cytoskeletonsupporting
confidence: 61%
“…This recovery was not observed when Tpm1 was overexpressed in cells that were treated with latrunculin B, which caused the disorganization of the actin network and impaired cellular motility. The expression of Tpm1 with a dipeptide N-terminal extension, mimicking the structural effects of Nt-acetylation (37), restored the cytoskeletal and motility defects induced by hNatB depletion (Fig. S4).…”
Section: Tpm1 Overexpression Partially Restores Actin Cytoskeletonmentioning
confidence: 90%
See 1 more Smart Citation